Persepsi Anak Nelayan terhadap Pekerjaan Orang Tua di Desa Jiko Port Kecamatan Motongkad Kabupaten Bolaang Mongondow Timur - Aling, Desiana; Aling, Djuwita R.R.; Rantung, Steelma V.; Pangemanan, Jeannette F.; Longdong, Florence V.; Sondakh, Srie J. (AKULTURASI, 2025)
Abstract The purpose of this study was to determine the perception of fishermen’s children towards their parents’ work in Jiko Port Village, Motongkad District, East Bolaang Mongondow Regency. The method used in this study is a qualitative method with a case study approach. This approach is considered appropriate because it can provide a deeper picture of the perception of fishermen’s children towards their parents’ work. The data collection method used Purposive sampling. This method is a sampling technique by determining certain criteria (Sugiyono, 2008). The data collected were primary data and secondary data. Primary data collection was carried out by means of interviews guided by questionnaires and observations. Secondary data collection was by citing existing data from related agencies or previous research. Data analysis used in this study was qualitative and quantitative descriptive analysis. Data analysis to determine fishermen’s perceptions used the Likert Scale. Respondents in this study were 20 male fishermen’s children in Jiko Port Village. The age of the fishermen’s children respondents aged 12-15 years was 4 people and 16-21 years was 16 people. Respondents’ education is junior high school 4 people and high school/vocational high school 16 people. There are 8 children who have graduated from vocational high school and did not continue to college, and 1 child has dropped out of school in grade 2 of vocational high school. Based on the results of the study, it was found that the perception of fishermen’s children towards their parents’ work in Jiko Port Village was 4.44, Perception of Family Welfare was 3.19, and the perception of Not Interested in becoming a fisherman obtained an average dimension score of 3.47. Keywords: perception, fishermen’s children, Jiko Village, fishermen Abstrak Tujuan penelitian ini adalah untuk mengetahui persepsi anak nelayan terhadap pekerjaan orangtua di Desa Jiko Port Kecamatan Motongkad Kabupaten Bolaang Mongondow Timur. Metode yang digunakan dalam penelitian ini adalah metode kualitatif dengan pendekatan studi kasus. Pendekatan ini dianggap tepat karena dapat memberikan gambaran yang lebih mendalam mengenai persepsi anak nelayan terhadap pekerjaan orang tua mereka. Metode pengambilan data menggunakan Purposive sampling. Metode ini merupakan teknik pengambilan sampel dengan menentukan kriteria-kriteria tertentu ( Sugiyono,2008). Data yang dikumpulkan yaitu data primer dan data sekunder. Pengumpulan data primer dilakukan dengan cara wawancara yang dipandu dengan kuisioner dan observasi. Pengumpulan data sekunder yaitu dengan mengutip data yang sudah ada dari instansi terkait ataupun penelitian yang terdahulu. Analisis data yang digunakan dalam penelitian ini adalah analisis deskriptif kualitatif dan kuantitatif, Analisis data untuk mengetahui persepsi nelayan menggunakan Skala Likert. Responden dalam penelitian ini adalah anak nelayan Laki-laki yang berada di Desa Jiko Port berjumlah 20 orang. Usia responden anak nelayan yang berusia 12-15 tahun berjumlah 4 orang dan 16-21 tahun berjumlah 16 orang. Pendidikan responden SMP 4 orang dan SMA/SMK 16 orang. Ada 8 anak yang sudah tamat di SMK dan tidak melanjutkan kejenjang perguruan tinggi, dan 1 anak sudah putus sekolah pada kelas 2 SMK. Berdasarkan hasil penelitian diperoleh bahwa persepsi anak nelayan terhadap pekerjaan orang tua di Desa Jiko Port sebesar 4,44, Persepsi Kesejahteraan Keluarga sebesar 3,19, Dan persepsi Tidak Tertarik untuk menjadi nelayan diperoleh skor rataan dimensinya sebesar 3,47. Kata kunci: persepsi,anak nelayan, Desa Jiko, nelayan